Synergistic effects of structural characteristics of quaternized polysulfone/cellulose acetate phthalate blends on surface properties - Onofrei Mihaela Dorina (Proceedings of the International Symposium on Analytical and Environmental Problems, 2016)
An alternative in order to obtain of new complex polymeric materials is represented by the blending polymers, thus creating a balance between the properties of individual components. New quaternized polysulfones (PSFQ)/cellulose acetate phthalate (CAP) blends were investigated for establishing the structural and compositional characteristics with impact on the surface properties. In this context, the synergistic effects generated by the charged groups from the alkyl radical of the quaternized polysulfones, flexible and hydrophilic nature of CAP in casting solution of polysulfone significantly influenced the surface tension parameters, surface free energy, and topographic reorganization. Moreover, the CAP composition, as well as the history of the formed films provide the controlling surface properties and are responsible for performance properties of the final membranes. In order to understand the correlation between the structural particularities and the resulting properties a deep analysis of the morphology must be performed.